Model Financial dan Teknologi (Fintech) Membantu Permasalahan Modal Wirausaha Umkm di Indonesia - Tedy Ardiansyah (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
The objectives of this study are (1) to find out the effect of technology-based financing models in helping entrepreneurial capital problems in society, Indonesia, (2) Knowing the types of technology-based financing models to help entrepreneurial capital problems in society, Indonesia, (3) Helping MSMEs capital in the future, (4) Helping solutions to business capital problems in entrepreneurial activities. Qualitative descriptive research is aimed at describing and describing existing phenomena, both natural and human engineering, which pay more attention to the characteristics, quality, and interrelationship between activities. In addition, this study does not provide treatment, manipulation or alteration on the variables studied, but describes a condition that is. Data collection techniques are derived from secondary data while the research instrument utilizing the results of the research that has been done both comes from journals, the Internet and books. From several research results illustrate that: (1) activities related to finance and technology are indeed needed by MSMEs with the current situation, (2) There is a relationship between financial and technological models (fintech) in helping MSME entrepreneurial capital problems, (3) Models financial and technology (fintech) consists of several kinds, among others: (a) crowd funding and peer to peer lending, (b) Market aggregator, (c) Risk and Investment Management and (d) Payment, settlement and clearing. (4) The results of research that greatly help MSME entrepreneurs in obtaining capital to maintain and improve business are financial and technology models (fintech) which lead to Crowd funding and Peer to Peer (P2P) lending, (5 in Indonesia are more familiar with P2P where has been implemented in activities including: (a) Agricultural Capital Startup, (b) Livestock Capital Startup and (c) Fisheries Capital Startup, (6) Future capital challenges have definite answers to the development of alias finance and technology fintech.